2016
DOI: 10.4103/0971-9784.185541
|View full text |Cite
|
Sign up to set email alerts
|

Simulation for transthoracic echocardiography of aortic valve

Abstract: Simulation allows interactive transthoracic echocardiography (TTE) learning using a virtual three-dimensional model of the heart and may aid in the acquisition of the cognitive and technical skills needed to perform TTE. The ability to link probe manipulation, cardiac anatomy, and echocardiographic images using a simulator has been shown to be an effective model for training anesthesiology residents in transesophageal echocardiography. A proposed alternative to real-time reality patient-based learning is simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Before incision, a thorough transesophageal echocardiography (TEE) examination was performed with the primary aim of evaluating the aortic root and ascending aorta. We confirmed the diagnosis of severe aortic stenosis and aortic regurgitation by Doppler echocardiography[ 3 ] [ Figure 1 ]. A closer look into our long axis imaging of aortic root revealed that there was an abrupt increase in the diameter of the root beyond the native sinotubular junction.…”
mentioning
confidence: 65%
“…Before incision, a thorough transesophageal echocardiography (TEE) examination was performed with the primary aim of evaluating the aortic root and ascending aorta. We confirmed the diagnosis of severe aortic stenosis and aortic regurgitation by Doppler echocardiography[ 3 ] [ Figure 1 ]. A closer look into our long axis imaging of aortic root revealed that there was an abrupt increase in the diameter of the root beyond the native sinotubular junction.…”
mentioning
confidence: 65%